W.M. S. Thorington, The Code of Ordinances of the City Council of Montgomery 225, § 518 (1888) - (:unkn) unknown (My University, 1888)
Any person who carries concealed about his person a bowie-knife or any other knife or instrument of like kind or description, or a pistol or fire-arms of any kind or description, or any air-gun, slung-shot, brass-knuckles, or any other deadly or dangerous weapon, must, on conviction, be fined not less than fifty, nor more than one hundred dollars; or may be sentenced to hard labor for the city for not more than one hundred days;
Keywords: CARRY - CONCEALED